Knowledge and Practice of Oncology Social Workers in the Management of Cancer Patients at UNTH Enugu, Enugu State, Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2023)
The increasing number of patients living with cancer as a chronic disease stresses the importance of paying attention to rehabilitative and psychosocial care which is the major role of oncology social workers. The study aimed at appraising the knowledge and practice of oncology social workers among cancer patients in UNTH. The study adopted the questionnaire and in-depth interview guide in generating data to answer research questions and test hypotheses. Responses to questionnaire were elicited from 574 respondents while the in-depth interview had 10 participants. Responses to questionnaire were analyzed quantitatively using SPSS version 20, while those for in-depth interview were analyzed thematically to complement the quantitative data. Hypotheses were tested using Chi-square (χ2), while the long-run significance of certain predictor variables on the dependent variable was ascertained using binary logistic regression. Findings from the study revealed that majority of respondents had no knowledge of oncology social work. Place of residence and level of education had significant relationship with knowledge of oncology social work at (p